Posisi Hassan dalam Reform Islam di Indonesia - Mughni, Syafiq A. (Qurthuba: The Journal of History and Islamic Civilization, 2017)
The progress of Hassan's attitude and thinking has prompted Muslims to revisit every custom and tradition that has been considered to be well established and taken for granted, as adopted by "traditionalists." Muslims have been challenged to be critical of criticism - his sharp criticism of every action and thought that does not come from the Qur'an and Sunnah. Hassan's challenge to critical thinking does not mean to invite people to anti-dogma. The challenge to secularists in the matter of secular nationalism also does not mean anti-modernity. However, Hassan is critical and upholds rationality based on Islamic teachings. Basically Hassan called on the ummah of Islam to return to the teachings of Islam that has long been forgotten by its own adherents that resulted in the decline and freeze of the ummah. that is the basis for the author to write an article with the title of Hassan Position In Islamic Reform in Indonesia